Assessing the Accuracy, Quality, and Readability of Online Patient Resources on Achilles Tendonitis. Issue 4 (November 2022) - Zhang, Hui; Cush, Coleman; Foster, Brian; Cush, Gerard J.
Category: Other; Hindfoot Introduction/Purpose: The internet is full of websites focused on different medical topics. With such a large accumulation of information, patients should be able to rely upon the internet as a reliable source for information on common medical conditions such as Achilles tendonitis. However, the question remains as to the accuracy, quality and readability of such online patient resources. Consumers themselves commonly evaluate online medical sites by trustworthiness, expertise, and objectivity. The purpose of this study was to investigate the top search-engine-generated online resources for Achilles tendonitis for their content and accuracy. Methods: The term 'Achilles tendonitis' was searched using the three most population search engines. The first 50 sites from each search were recorded. Duplicate sites were eliminated. Sites were categorized based on authorship type. Each website was independently evaluated by two reviewers. Quality was evaluated utilizing the DISCERN score and the Journal of the American Medical Association (JAMA) benchmark criteria. Accuracy was evaluated using a novel Achilles tendinosis-specific content rubric developed with a foot and ankle fellowship-trained orthopaedic surgeon and the AAOS OrthoInfo webpage, similar to previous studies. Readability was evaluated using the Flesch Kincaid grade level (FKGL) and Flesch Reading Ease (FRE) formulas. Higher FRE scores indicate better readability. FKGL was also compared against an 8th grade level, which represents the average US reading level. Results: The search resulted in 77 unique websites with 60 sites included for analysis. The average DISCERN score in our investigation is 42.1 which places it in the 'fair' category. Commercial websites were found to have higher DISCERN scores as compared to websites created by physicians or medical groups as well as academic websites. Our study found an average JAMA quality benchmark score of 2.2 out of 4. Our study found that on average, online patient resources on Achilles tendinosis was written at a 9th grade reading level with a FKGL score of 9.8. Academic websites were found to be written at a significantly lower reading level of 8.8. The average FRE score was 53.28 which translates to the 'fairly difficult' category. Utilizing our own content scoring system to assess the accuracy of online resources, the websites had an average accuracy of 11.5 points out of 20 possible points. Conclusion: The average online patient resource on Achilles tendinosis is too complex for the average patient, inaccurate, and is of low quality. This study found that the average website had low quality as measured by the DISCERN and JAMA benchmark scores. The average accuracy was also low as measured by our novel content specific score. The websites were also difficult to read as measured by the FRE and FKGL scores. More emphasis on improving the readability, quality, and accuracy of online patient resources on Achilles tendinosis should be undertaken in order to improve patient healthcare.